Finance and Development, September 1982. (Finance and Development; Finance and Development, 1982)
This paper highlights that there has been remarkable agricultural growth over the past three decades. Growth has been twice as rapid as in any previous period. Output has been fueled largely by developing countries' increased capacity to produce more food and by continued growth in the developed countries. Despite this remarkable and sometimes unrecognized achievement, the 'world food problem' continues to haunt mankind. Population growth, more rapid than agricultural growth in many poor countries, has sharply reduced the per capita benefits of increased food production.